A Comparative Study between Ultrasound-guided Concomitant Infraclavicular Plus Distal Median, Radial, and Ulnar Nerve Blockade Versus Infraclavicular Block Alone - T Jaya Priya; TG Sivathangavel; K. Soundarya Priyadharsini; T. Krishna Prasad (Journal of the Scientific Society)
Background: Peripheral nerve blocks can be used alone as the sole ‘surgical’ anesthetic technique as the initial step in providing prolonged postoperative analgesia. There are studies, where accurate deposition of local anesthetic perineurally has the potential to improve the success rate and reduce the incidence of complications of the infraclavicular block. We hypothesized whether a combined block of the infraclavicular brachial plexus and distal median, radial, and ulnar nerves would accelerate upper extremity anesthesia compared with an infraclavicular block alone. Materials and Methods: This study was a prospective randomized control study conducted among 60 patients undergoing elective and emergency wrist and hand surgeries. A group of 30 patients received an infraclavicular block with 30 mL of a local anesthetic mixture containing 1% lignocaine with adrenaline and 0.25% bupivacaine from Group A. Group B received an infraclavicular block with 15 mL of local anesthetic mixture containing 1% lignocaine with adrenaline and 0.25% bupivacaine along with distal median, radial, and ulnar nerve blockade with 5 mL each of local anesthetic mixture containing 1% lignocaine with adrenaline and 0.25% bupivacaine. Pain score, assessment of sensory and motor functions, block performance time, and surgical anesthesia were observed. Results: The mean block performance time of Group A was 10.9 ± 1.1 min and Group B was 14.7 ± 0.5 min. The difference between the two groups’ block performance minutes was statistically significant (P < 0.001). The difference in the onset of the sensory block between the two groups was statistically significant (P < 0.001). The mean onset of motor blockade between the two groups was statistically very highly significant (P < 0.001). The mean of Group A was 5.0 ± 0.2 and Group B was 2.1 ± 0.4. Conclusion: From this study, we conclude that using an approximately equivalent dose of local anesthetics, combining ultrasound-guided infraclavicular block with distal median, radial, and ulnar nerve blockade shortens the onset time of sensory and motor block with improved block consistency compared to infraclavicular block alone.